A study on chloronitrobenzene manufacture wastewater treatment with sequential anaerobic-aerobic process - YE Min; XU Xiang-yang; XIE Yu-sheng (浙江大学学报. 农业与生命科学版, 2003)
The performances and mechanism of Fe/C reduction-A/O process for the treatment of chloronitrobenzenes manufacture wastewater were studied in this paper. The results showed that main pollutants in effluent from integrated process were up to the second standard of GB8978-96 at influent COD 1241-1608 mg/L, nitrobenzene 52.0-69.2 mg/L, aniline 161.1-260.2 mg/L, when HRT was set up to be 1 h in Fe/C reduction unit, 10-12 h / 36-48 h in the anoxic / anaerobic biological reactors, respectively, and addition of 0.5-2‰ FeCl3 as the post-treatment agent. The GC-MS analytical results indicated the typical toxic organic pollutants, such as chloronitrobenzene, chloroaniline, and aniline were transformed and decomposed in this integrated process, mechanism of organics transformation and degradation by Fe/C or microorganism was also suggested.